121k views
19 votes
Help with this question (100 points)

Help with this question (100 points)-example-1
User Thesmart
by
5.1k points

2 Answers

6 votes


\\ \rm\Rrightarrow sin(x+y)=(1)/(2)sinx+(√(3))/(2)cosx


\\ \rm\Rrightarrow sinxcosy+cosxsiny=(1)/(2)sinx+(√(3))/(2)cosx

  • Cancel sin and cos


\\ \rm\Rrightarrow cosy+siny=(1)/(2)+(√(3))/(2)


\\ \rm\Rrightarrow cos(\pi)/(3)+sin(\pi)/(3)=(1)/(2)+(√(3))/(2)

  • y=π/3

Option B

User Goddogsrunning
by
5.0k points
3 votes

Answer:

y =
(\pi)/(3)

Explanation:

using the addition formula for sine

sin(x + y) = sinxcosy + cosxsiny

then

sinxcosy + cosxsiny =
(1)/(2) sinx +
(√(3) )/(2) cosx

for the 2 sides to be equal , then

cosy =
(1)/(2) and siny =
(√(3) )/(2)

then

y =
cos^(-1) (
(1)/(2) ) =
(\pi )/(3)

and

y =
sin^(-1) (
(√(3) )/(2) ) =
(\pi )/(3)

thus y =
(\pi )/(3)

User Stralsi
by
5.0k points